Peningkatan Kompetensi Back End Web Programming: Pelatihan Bahasa Pemrograman JavaScript bagi Mahasiswa - Muhammad Fardan; Dary Mochamad Rifqie; Rosidah Rosidah; Akhmad Affandi; Sudarmanto Jayanegara; M. Miftach Fakhri (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
The program proposes and evaluates the implementation of a training titled "Enhancing Competence in Back End Web Programming: JavaScript Training for Students" with the aim of preparing students in web programming competency in the back end domain. A preliminary study is conducted to analyze the initial competency level of students in JavaScript, which serves as the basis for designing a suitable training program. The program is implemented according to the established plan and schedule, while evaluation is carried out by monitoring participant participation and their responses during the socialization activities. The research results are expected to provide an understanding of the effectiveness of the program in enhancing JavaScript skills for back end website development. The conclusions drawn from this research are expected to provide a foundation for the development of students' web programming competencies, particularly in the use of JavaScript for back end development.